Physiological profiles and training loads of international level male and female cross-country skiers and biathletes - Myakinchenko, E. B.; Heil, D. P.; Kriuchkov, A. S.; Feoktistov, V. V.; Kuzmichev, V. A.; Adodin, N. V. (Science & Sports, 2022)
Objective The aim was to investigate physiological profiles of elite male and female cross-country skiers and biathletes in the context of their annual training load volumes and whether this explained differences in racing speeds. Methods 108 Russian athletes (International rank: 2-211) were divided into four groups (cross-country skiers and biathletes, males and females), matched for age. Fitness assessment included 33 anthropometrics, aerobic, anaerobic, strength, and gross-efficiency of upper-body and lower-body parameters. Training load volumes included 21 endurance, strength, power, sport-specific, and non-specific parameters averaged over 2014-2020. Results Cross-country skiers significantly exceeded biathletes in strength (X ± SD: 81 ± 12 vs 45 ± 12 hours, P < 0.001) and endurance training load volumes (779 ± 42 vs 547 ± 40 hours, P < 0.001). Cross-country skiers had higher: body mass index (23.0 ± 3.3 vs 22.4 ± 1.8, kg/m2, P = 0.008); upper-body and running ventilation thresholds (50.1 ± 7.9 vs 46.2 ± 5.4, and 62.5 ± 4.0 vs 60.5 ± 6.7 mL/min/kg, P < 0.001), but equal V?O2max and gross-efficiency. Male and female athletes had equal volumes of endurance and strength training loads, but females tended to have lower values of training intensity. Gender upper-body and lower-body differences were greater for aerobic and anaerobic power but smaller for strength.